The biomechanics of kicking in soccer: A review - Lees, A.; Asai, T.; Andersen, T. B.; Nunome, H.; Sterzing, T. (Journal of Sports Sciences, 2010)
Kicking is the defining action of soccer, so it is appropriate to review the scientific work that provides a basis of our understanding of this skill. The focus of this review is biomechanical in nature and builds on and extends previous reviews and overviews. While much is known about the biomechanics of the kicking leg, there are several other aspects of the kick that have been the subject of recent exploration. Researchers have widened their interest to consider the kick beginning from the way a player approaches the ball to the end of ball flight, the point that determines the success of the kick. This interest has encapsulated characteristics of overall technique and the influences of the upper body, support leg and pelvis on the kicking action, foot-ball impact and the influences of footwear and soccer balls, ball launch characteristics and corresponding flight of the ball. This review evaluates these and attempts to provide direction for future research.